TEACHING STRATEGIES IMPLEMENTED BY ENGLISH EDUCATION DEPARTMENT LECTURERS OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA TO IMPROVE STUDENT’S VOCABULARY - Trisnawati (PBI 15 UMY 039, 2015)
*39 Strategy to teach vocabulary is really important to improve students’ vocabulary in the learning process. The aim of this research was to investigate the teaching strategies implemented by English Education Department lecturers Universitas Muhammadiyah Yogyakarta (EED UMY) to improve students’ vocabulary. This research employed qualitative research design which was a case study and used interviews to collect the data. The participants of this research were three lecturers of EED UMY who had been teaching English for more than nine years. All data were analyzed by using open coding, axial coding and selective coding. Based on the finding, this research revealed that each lecturer had used their own teaching strategies to improve students’ vocabulary. There were reading activities which were including pre-reading activity, predicting, retelling, quiz activity. Other teaching strategies were list of vocab, translating, and missing lyric. The result also showed that each lecturer had some obstacles in improving students’ vocabulary that were coming from the students who did not want to read a book given by lecturers and did not independently improve their vocabulary and time limitation. Each lecturer had their own strategies to solve their obstacles. Namely, lecturers gave some suggestions, motivations and encouragement to the students, so the students can improve their vocabulary